From Terra Ignota to historical landscapes in Patagonia : Practices, places and roads in peopling process - Miotti, Laura Lucía (2022)
The human colonization of an unknown environment is a complex and extensive process where individual, social, material and symbolic practices that are carried out, transform a space without history into a humanized and signified landscape.Understanding colonization as a process of environmental-social learning, the archaeological expectation is to find areas of routinization of individual and collective habits, and transit areas with specific indicators of logistic activities (routes, transitory camps, places of sighting and control, hunting sites). However, for this initial stage of peopling, the resolution grain of the archaeological record is usually coarse, and shows only partially the variability of routines and changes that produce regional colonization narratives.In this work we analyze the changing distribution of roads and places with the aim of sketching the changes in the structuring of the archaeological landscapes of colonization. The time considered encompasses the Holocene-Pleistocene transition/Early Holocene (ca. 12 – 8.5 ka BP). The geography corresponds to the Central Plateau in the province of Santa Cruz, and the Somuncura Massif in the province of Río Negro, Argentina. The localities of Los Toldos, Piedra Museo, La Primavera and Amigo Oeste are central archaeological references. The methodology used focuses on GIS to model the movement of objects, information and people in a network of possible paths to test the hypothesis of an initial northern and eastern coastal migration/s that advanced inland towards Los Andes foothills. We state that the archaeological record on local and regional scales of the Patagonian plateau allows us to approximate an idea of environmental learning processes in the archaeology of colonization.